The role of L1-L2 dissimilarity in L2 segment learning – Implications from the acquisition of English post-alveolar fricatives by Mandarin and Mandarin/Wu speakers - Chen, Wenjun; van de Weijer, Jeroen (Frontiers in Psychology, 2022)
This study examines how the concept of L1-L2 dissimilarity should be addressed from a two-way perspective in L2 segment learning, and how it relates to the learning outcomes. We achieved this by investigating the productions of the post-alveolar fricatives /ʃ, ʒ/ by Mandarin and Mandarin/Wu speakers, which were subsequently assessed by native English listeners. In the first experiment, we analyzed the spectral moments of /ʃ, ʒ/ produced by Mandarin monolingual and Mandarin/Wu bilingual speakers to find out how the two groups of speakers pronounced the target segments. In the second experiment, native English listeners were tasked with rating the accentedness of the Mandarin- and Mandarin/Wu-accented /ʃ, ʒ/. Results showed native English listeners scored Mandarin/Wu-accented /ʃ/ as having no accent and Mandarin-accented /ʒ/ as having a heavy accent, indicating that English natives perceived the ‘native vs. nonnative’ segment dissimilarity differently from Chinese learners of English, and that the L1-L2 dissimilarity perceived from both sides may work together in defining the L2 segment learning outcomes.